Analysis Of The Application Of Data Mining Using The C4.5 Algorithm Method For Data Collection On Permanent Employees In North Sumatera Coni - Gina Sonia; Indriyani, Agil (Journal of Computer Science and Informatics Engineering, 2023)
Koni Sumut is a sports company, there are many employees at Koni Sumut, it takes a relatively long time to register regular employees during the manual inspection process. Companies have difficulty determining which employees will be prioritized. The problem is that the manager does not use a method that can handle the problem of multiple priority criteria. In addition, HR often has difficulty in selecting permanent employees because of the large number of employees that must be evaluated. This is what is lacking in deciding whether someone will be elected as a permanent employee or not. Applying data mining with the C4.5 algorithm method can increase the speed and level of accuracy in personal evaluation decisions. The test results obtained by the C4.5 algorithm have good precision, accuracy and recall values. Keywords: Koni Sumut, Data Mining, C4.5 . Algorithm